Socio-psychological Determinants for Technology Socialisation of Jute Production in West Bengal (Indian Journal of Extension Education, 2022)
Jute is a major commercial crop grown by majority of the small and marginal farmers of West Bengal. To make this venture profitable ICAR-Central Research Institute of Jute and Allied Fibres (CRIJAF) had developed innovative jute production technologies. The study was conducted during 2021 at villages of North 24 Parganas and Nadia districts of West Bengal where ICAR-CRIJAF had disseminated its innovative technologies. A sample of 160 jute growers comprising of 80 adopter farmers and 80 non-adopter farmers were selected randomly. The objective was to identify the influence of the socio-psychological characteristics of the jute growers on their level of technology socialisation. Canonical correlation analysis was carried out to find the association between these two sets of variables. The variables; achievement motivation, innovativeness, education, land holdings etc. moved together with adoption whereas farming experience and age followed the same direction as rejection and discontinuance.